2016
DOI: 10.1080/13548506.2016.1238493
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, depression, & stress: predictors of fibromyalgia health status

Abstract: The purpose of the present study was to examine the effects of smoking, stress, and depression on fibromyalgia health status. Fibromyalgia syndrome (FMS) is a chronic musculoskeletal pain condition that negatively affects health status. Health status is not only affected by the constellation of physical symptoms, but also by mood symptoms, stress levels, and patient behaviors (e.g. smoking). Participants were 491 individuals with a physician's diagnosis of FMS. They completed self-report measures of their curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The characteristic features of the FM patients are in agreement with other studies that showed a positive family history and smoking. [ 22 23 ] These observations indicate that FM is a disease that related to the genetic disorder, and the smoking behavior is a reaction to stress. The values of MPV and platelet width distribution were significantly higher in FM patients than healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic features of the FM patients are in agreement with other studies that showed a positive family history and smoking. [ 22 23 ] These observations indicate that FM is a disease that related to the genetic disorder, and the smoking behavior is a reaction to stress. The values of MPV and platelet width distribution were significantly higher in FM patients than healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…FM patients exhibit a higher preva- lence of smoking, indicating that this population faces a heightened health hazard. Furthermore, smoking may potentially impact pain perception or pain management strategies (16)(17)(18)(19)(20)(21). The higher prevalence of lower education levels among FM patients suggests that socioeconomic variables may exert a substantial influence on the risk and management of FM.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Individuals who experience a greater degree of stress exhibit elevated scores for fibromyalgia severity, as per previous research. [27] It is posited that the augmented severity of fibromyalgia in mothers of children with Autism Spectrum Disorder (ASD) in comparison to mothers of neurotypical children may be attributed to an excessive burden of stress.…”
Section: Discussionmentioning
confidence: 99%